Using health belief model to predict oral health behaviors in girl students: A structural equation modeling. Issue 1 (April 2020) - Ashoori, Fatemeh; Karimi, Masoud; Mokarami, Hamidreza; Seif, Mozhgan
Abstract: Introduction: Dental caries and gum diseases are among the most common oral diseases in children around the world especially in less developed countries. Evidences suggest that identifying the reasons for not following the oral health behaviors, can improve the oral health status through evidence based interventions. The aim of this study was developing a model to explain the predictors of oral health behaviors in primary school girl students Based on the health belief model. Methods: In this cross-sectional analytical study conducted in 2018, a total of 381 questionnaires were distributed among all fifth and sixth grade girl students of public schools in Lamerd, Iran. The data were collected through a researcher-made questionnaire included demographic information, and health belief model constructs (Cronbach's alpha between 0.54 and 0.77). Data were analyzed by SPSS23 and AMOS 23 for structural equation modeling. Results: A total of 179 fifth-grade and 180 sixth-grade girl students participated in the study (94.2% response rate). More than 35% and 67% of students in the study did not brush and floss daily respectively. Perceived barriers (r = -0.27, P < 0.01), self-efficacy (r = 0.32, P < 0.01) and cues to action (r = 0.26, P < 0.01) showed significant correlation with behaviors. In final model by SEM, self-efficacy, perceived barriers, and cues to action have the highest relationship with oral health too. Other model constructs showed no significant relationship with behavior. Conclusion: The results suggest the necessity to emphasize the perceived benefits, self-efficacy and cues to action to promote students' oral health behaviors.